2018
DOI: 10.1177/0020764018776350
|View full text |Cite
|
Sign up to set email alerts
|

Need for information in a representative sample of outpatients with schizophrenia disorders

Abstract: Information was a commonly reported need and which was often unmet, showing no significant association with service use. Greater attention should be given by mental health services to information provision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In the present study, there was no significant relationship between patients' needs (including met and unmet needs) and patients' age. This was consistent with other similar studies that did not report an association between age and the needs of patients with severe psychiatric disorders ( 27 , 30 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, there was no significant relationship between patients' needs (including met and unmet needs) and patients' age. This was consistent with other similar studies that did not report an association between age and the needs of patients with severe psychiatric disorders ( 27 , 30 ).…”
Section: Discussionsupporting
confidence: 93%
“…In a study by Ashour et al to explore the relationship between sex and the needs of patients with schizophrenia, although the total number of needs of women was reported to be higher than men, this relationship was not statistically significant ( 27 ). In another study, there was a significant relationship between the level of education and the needs of patients with schizophrenia; thus, the higher the level of education, the lower the number of unmet needs ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study compared the needs of patients in five European countries (20) and found that the mean number of needs in each country ranged from 6.3 to 4.8, and the most frequently reported unmet needs were related to company, intimate relationships, and psychological distress. In LMICs, countries such as Kuwait, India, and Brazil, the most frequently reported unmet needs were related to money, education, accommodation, and information (2,(22)(23)(24), which seem to be more associated with possible socioeconomic disadvantages than with the severity and prognosis of the mental disorder itself.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the high prevalence of mental disorders ( 1 - 3 ) contrasts with the mental health expenditure, which is less than 1% of the national health budget ( 4 ), with the implementation of effective community-oriented mental health care still an ongoing process ( 5 ). Thus, identifying of possible barriers to appropriate treatment for each person and specific population groups is an important step to guide the application of scarce resources ( 6 ).…”
Section: Introductionmentioning
confidence: 99%